KOMUNIKASI PEMASARAN DALAM INDUSTRI GIM PASCA COVID-19: TINJAUAN SISTEMATIS DENGAN METODOLOGI PRISMA - I Ketut Gunarsa; Heru Prasetyo (Journal of Innovation Research and Knowledge, 2025)
This study examines the development of the marketing communication within the video game industry following the COVID-19 pandemic through a systematic literature review, employing the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) methodology. In response to the rapid digitalization triggered by COVID-19, companies have shifted how they engage with audiences by adopting new strategies such as social media, livestreaming, Esports, and narrative-building in online spaces. Academic studies have identified an expansion in the video game literature, however, notable gaps remain. By analyzing peer-reviewed literature from 2018 onward, this study identifies trends and discourses. Findings reveals that, although marketing strategies have changed, current academic discussions are fragmented and lack integration. Future studies should focus on distinguishing pre- and post-COVID-19 strategies to emphasize their relevance and develop comprehensive framework capable of analyzing the interdisciplinary nature of this field